A DIGITAL TRANSFORMATION IN PUBLIC SERVICES: CHALLENGES AND OPPORTUNITIES (UNLOCKING EFFICIENCY AND ENGAGEMENT: EMBRACING INNOVATION IN GOVERNMENT OPERATIONS) - Sunatorn, Patcharaporn (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the integration of advanced digital technologies—namely artificial intelligence (AI), cloud computing, and the Internet of Things (IoT)—into public service delivery to enhance operational efficiency, cost-effectiveness, and citizen engagement. Method: Employing a qualitative case study approach, the research analyzes multiple government initiatives, including Worcestershire District Chambers’ rapid application development and Germany’s digitalization of 575 public services, to identify benefits and challenges of digital transformation in the public sector. Results: Findings reveal significant advantages such as streamlined service delivery via online portals and e-signatures, increased transparency through open data platforms, and improved interagency collaboration enabled by cloud-based tools. However, barriers including constrained budgets, legacy systems, regulatory complexities, and resistance to change remain substantial challenges. Novelty: This report contributes a comprehensive framework emphasizing a strategic, incremental implementation supported by effective change management and stakeholder engagement to overcome obstacles. It highlights the importance of aligning digital initiatives with public value principles, ethical data practices, and cross-sector collaboration to realize sustainable transformation in public services. The insights advance understanding of how governments can leverage emerging technologies to create more inclusive and efficient public administration.